The Effect of Lending and Placement of Funds in Other Banks on the Bank's Ability to Increase Profitability - Nasfi; Eka Febrianti; Asnah; Sabri (Yayasan Ilomata, 2020)
This study aims to determine and analyze the effect of lending and placement of funds in other banks on the ability of banks to increase profitability. The study was taken data from one of the XYZ micro banking institutions in West Sumatra, based on year-end financial data from 2009 to 2019. This research uses a quantitative approach. The data source used is secondary data in the form of financial statement data for micro banking institutions for 11 (eleven) years. The data analysis method uses the Ordinary Least Square (OLS) method. The results showed that partially lending had a negative and significant effect on increasing profitability, placement of funds in other banks had a negative and insignificant effect on the increase in profitability of XYZ micro banking. Simultaneously, the variable of credit distribution and placement of funds in other banks has a significant effect on the increase in profitability of the XYZ micro banking institution